Intention Versus Uptake: LARC Among Postpartum Women in a Federally Qualified Health Clinic [17J]. (May 2020) - Freeman, Emily; Heiselman, Cassandra; Bacak, Stephen; Knebusch, Madeleine; Cottrell, Connie
Abstract : INTRODUCTION: Access to full spectrum contraceptive methods, including long-acting reversible contraception (LARC), is critical for preventing unintended and short-interval pregnancy. Despite serving a population at high risk for unintended pregnancy, federal qualified heath centers (FQHC) often have limited access to LARC on-site and at associated hospitals that may impact contraceptive utilization. The goal of the study was to examine access and barriers to LARC uptake among women at a FQHC. METHODS: We conducted a retrospective chart review of all women seen for antenatal care at a single resident run FQHC from 2014 to 2017. Women age 18-40 and who delivered at the associated hospital were included. The FQHC offered intrauterine device (IUD) but did not offer contraceptive implant placement. The associated hospital did not provide immediate postpartum LARC during the study period. RESULTS: In our study, 560 women were identified. There was a 60.5% postpartum follow-up over the study period. 65% (n=364) had documentation of a confirmed postpartum contraception plan prior to delivery. Of women with a plan, 27% (n=100) expressed desire for postpartum LARC. Only 21% (n=21) of women who desired LARC actually received LARC within the first 6 months after delivery. All IUDs were received at the FQHC. No women received a contraceptive implant at an outside facility. CONCLUSION: Our data suggests that when LARC options are not readily available, postpartum uptake is poor regardless of intention. Therefore, strategies need to be developed to improve access to all LARC methods, including expanding immediate postpartum services and improving antepartum contraception counseling.